Early Relative Hypotension Below Noninvasive Cerebral Oximetry-Derived Optimal Blood Pressure Thresholds in Aneurysmal Subarachnoid Hemorrhage: A Pilot Study - Shah, Vishank A; Humayun, Mariyam; Radzik, Batya; Healy, Ryan; Palmisano, Caitlin; Anderson-White, Mirinda; Calvillo, Eusebia; Geocadin, Romergryko; Brown, 4th, Charles; Hogue, Charles; Ziai, Wendy; Cho, Sung-Min; et al. (Critical care medicine, 2025)
Impairment in cerebral autoregulation (CA) after aneurysmal subarachnoid hemorrhage (aSAH) is associated with delayed cerebral ischemia (DCI) and poor outcomes. We assessed: 1) feasibility of defining CA-based optimal mean arterial pressure (MAP Opt ) thresholds using noninvasive cerebral oximetry and 2) associations of relative hypotension below MAP Opt in the early brain injury (EBI) and pre-DCI phase with DCI and long-term outcomes after aSAH. Pilot observational study on a prospective cohort. Single-center Neuro-ICU. aSAH patients with altered consciousness. Continuous noninvasive cerebral oximetry neuromonitoring. Daily MAP Opt was defined as observed MAP (MAP Obs ) corresponding to lowest cerebral oximetry-derived autoregulation index. Outcomes included DCI and 1-year modified Rankin Scale (mRS). Mixed-effects linear regression assessed MAP Opt trajectories. Multivariable generalized estimating equation models assessed associations between daily %time below MAP Opt ± 5 mm Hg (MAP Opt range) and DCI and poor 1-year mRS (mRS 4-6). We included 118 daily MAP Opt measurements (118/128 epochs = 92.2% feasibility) estimated from 35 aSAH patients receiving cerebral oximetry monitoring for median duration of 4 days (interquartile range [IQR], 3-4 d), beginning on median of hospital day 2 (1-3). Median (IQR) age was 64 years (52-69 yr), World Federation of Neurological Surgeons grade 4 (2-5), and modified Fisher Scale 4 (3-4). DCI and poor 1-year outcome occurred in 15 (42.9%) and 20 (57.1%) patients, respectively. Patients that developed DCI had higher median MAP Opt (102.5 vs. 85 mm Hg; p = 0.03), upward trajectory of MAP Opt (β-coefficient = +19 mm Hg; p = 0.04 vs. +4 mm Hg; p = 0.56), and greater %time with MAP Obs below MAP Opt range (39.7% vs. 12.7%; p = 0.01) in the early phase. In covariate-adjusted models, %time below MAP Opt range was independently associated with DCI and poor 1-year mRS (adjusted odds ratio, 1.02; 95% CI, 1.002-1.03; p = 0.03). Defining individualized MAP Opt thresholds using noninvasive cerebral oximetry was feasible. Relative hypotension below oximetry-based MAP Opt in the EBI and pre-DCI phase (days~2-6) was associated with DCI and poor long-term functional outcome, supporting further exploration of individualized hemodynamic optimization in the early phase of aSAH.